Analisis Kelayakan Usaha Pada Unit Usaha Simpan Pinjam Di Desa Induk Kecamatan Bantan Kabupaten Bengkalis - Maharani, Desy; Sri Wahyuni, Endang (P3M Politeknik Negeri Bengkalis, 2024)
This study aims to analyze the business feasibility of the Unit Usaha Simpan Pinjam (USP) in Induk Village, Bantan District, Bengkalis Regency, with a focus on assessing the potential for reinvestment from a financial and non-financial perspective. The research method used is a qualitative approach, with primary and secondary data collection through a purposive sampling technique that targets USPs with high capital. The investment feasibility analysis was conducted by reviewing non-financial aspects, including legal, socioeconomic and environmental aspects, market and marketing, and management and human resources. Financial aspects were analyzed using investment evaluation tools such as Net Present Value (NPV), Internal Rate of Return (IRR), Payback Period (PP), and Profitability Index (PI). The results showed that the USP in Desa Induk is feasible from both non-financial and financial aspects. The positive NPV, PI of more than 1, and reasonable PP indicate that the investment is profitable. However, the IRR of only 11% is still below the Minimum Acceptable Rate of Return (MARR) of 13.25%, indicating a need to improve operational efficiency. Nonetheless, the main objective of the USP development focuses more on improving the economic welfare of village communities rather than solely achieving financial returns.The USP development strategy includes a sustainable approach that is oriented towards improving the welfare of the villagers.